Effects of drop height on jump performance in male and female elite adolescent handball players - Prieske, O.; Chaabene, H.; Puta, C.; Behm, D. G.; Büsch, D.; Granacher, U. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To examine the effects of drop height on drop-jump (DJ) performance and on associations between DJ and horizontal-jump/sprint performances in adolescent athletes. Methods: Male (n = 119, 2.5 [0.6] y post-peak-height velocity) and female (n = 120, 2.5 [0.5] y post-peak-height velocity) adolescent handball players (national level) performed DJs in randomized order using 3 drop heights (20, 35, and 50 cm). DJ performance (jump height, reactive strength index [RSI]) was analyzed using the Optojump Next system. In addition, correlations were computed between DJ height and RSI with standing-long-jump and 20-m linear-sprint performances. Results: Statistical analyses revealed medium-size main effects of drop height for DJ height and RSI (P < .001, 0.63 = d = 0.71). Post hoc tests indicated larger DJ heights from 20 to 35 and 35 to 50 cm (P = .031, 0.33 = d = 0.71) and better RSI from 20- to 35-cm drop height (P < .001, d = 0.77). No significant difference was found for RSI between 35- and 50-cm drop height. Irrespective of drop height, associations of DJ height and RSI were small with 5-m-split time (-.27 = r = .05), medium with 10-m-split time (-.44 = r = .14), and medium to large with 20-m sprint time and standing-long-jump distance (-.57 = r = .22). Conclusions: The present findings indicate that, irrespective of sex, 35-cm drop heights are best suited to induce rapid and powerful DJ performance (ie, RSI) during reactive strength training in elite adolescent handball players. Moreover, training-related gains in DJ performance may at least partly translate to gains in horizontal jump and longer sprint distances (ie, =20-m) and/or vice versa in male and female elite adolescent athletes, irrespective of drop height.